Antibiotic therapy as personalized medicine – general considerations and complicating factors. Issue 5 (24th May 2019) - Moser, Claus; Lerche, Christian Johann; Thomsen, Kim; Hartvig, Tom; Schierbeck, Jens; Jensen, Peter Østrup; Ciofu, Oana; Høiby, Niels
Abstract : The discovery of antibiotic drugs is considered one of the previous century's most important medical discoveries (Medicine's 10 greatest discoveries. New Haven, CT: Yale University Press, 1998: 263). Appropriate use of antibiotics saves millions of lives each year and prevents infectious complications for numerous people. Still, infections kill unacceptable many people around the world, even in developed countries with easy access to most antibiotic drugs. Optimal use of antibiotics is dependent on the identification of primary and secondary focus, and knowledge on which pathogens to expect in a specific infectious syndrome and information on general patterns of regional antibiotic resistance. Furthermore, sampling for microbiological analysis, knowledge of patient immune status and organ functions, travel history, pharmacokinetics and ‐dynamics of the different antibiotics and possible biofilm formation are among several factors involved in antibiotic therapy of infectious diseases. The present review aims at describing important considerations when using antibacterial antibiotics and to describe how this is becoming substantially more personalized. The parameters relevant in considering the optimal use of antibiotics to treat infections are shown in Fig. 1 – leading to the most relevant antibiotic therapy for that specific patient. To illustrate this subject, the present review's focus will be on challenges with optimal dosing of antibiotics and risks of underdosing. Especially, in cases highly challenging for achieving the aimed antibiotic effect against bacterial infections – this includes augmented renal clearance (ARC) in sepsis, dosing challenges of antibiotics in pregnancy and against biofilm infections.